Karakteristik Penderita Ileus Obstruktif - Dwi Oktaviani Dana Reksa; Abdul Aziz; Fajar Amansyah (2025)
Bowel obstr.uction c.an b.e .a mech.anical o.r func.tional bloc.kage o.f t.he sm.all o.r larg.e bowel. Cau.ses .of i.leus o.bstruction i.n th.e sm.all bo.wel .include incarce.rated her.nia, intestinal adhesions, invaginations (intusjsusception), asjcariasis, volvjulus, tumors, galljstones thjat entjer thje ijleus. Obstjruction often causes abdominal pain, nausea, vomiting, constipation, . obstipation and distension. Intestinal obstruction refers to when the intestinal lumen becomes par.tially o.r comp.letely b.locked. S.mall bo.wel obstruction (SBO) is m.ore comm.on tha.n la.rge bowel obstruction (LBO) and is the most frequent indication f.or surge.ry on the .small bowel. Thjis litejrature rejview aijms tjo deterjmine th.e char.acteristics .of pat.ients with obstructive ileus. Thje metjhod usejd ijs literajture rejvi.ew wjith Narrjative Rjeview des.ign. Th.e res.ults obtain.ed ijn tjh.is litjerature ajre tjhat tjhere ajre 10 artjicles obtjained wjith restrjictions frojm 2020 - 2025 anjd ajn i.n-de.pth analy.sis ojf tjhe sjtrengths anjd limitatijons ojf eajch .artijcle regjarding tjhe charactejristics ojf ob.structive ileus p.atients, 10 articl.es men.tion the characteristics of obstructive ileus patients... The risk of developing intestinal obstruction at a given age varies depending on when symptoms appear and the cause of the obstruction. I.n th.e eld.erly popu.lation, o.vejr thj.e ajg.e oj.f 5j0, there is a higher risk of developing tumors of the gastrointestinal tract.